2010
DOI: 10.1080/10937401003751630
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Selected Brominated Flame Retardants to Affect Neurological Development

Abstract: Various brominated flame retardants (BFR), including polybrominated diphenyl ether (PBDE) congeners, hexabromocyclododecane (HBCD), and tetrabromobisphenol A (TBBPA), are commonly used in household items and electronics and have been detected in the environment and/or the bodily fluids of people, including children. Some studies in animals suggest that exposure to PBDE congeners, HBCD, or TBBPA during the perinatal period may affect locomotor activity and/or memory and learning. Epidemiological studies showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 96 publications
(196 reference statements)
5
38
0
1
Order By: Relevance
“…The NOEL for these changes is 10 mg/kg BW/day. These findings are consistent with the observations of an extensive review of currently available TBBPA neurological data by Williams and DeSesso (2010) that demonstrated no adverse effects attributable to TBBPA exposures up to and including 1000 mg/kg BW/day on neurodevelopment, neuromotor functions, learning, memory, and neurobehavioral endpoints. It is noteworthy that thinning of the brain parietal cortex in the F 2 generation at post-natal day (PND) 11 was not associated with lesions or changes that were detectable by H&E histological examination.…”
Section: Discussionsupporting
confidence: 92%
“…The NOEL for these changes is 10 mg/kg BW/day. These findings are consistent with the observations of an extensive review of currently available TBBPA neurological data by Williams and DeSesso (2010) that demonstrated no adverse effects attributable to TBBPA exposures up to and including 1000 mg/kg BW/day on neurodevelopment, neuromotor functions, learning, memory, and neurobehavioral endpoints. It is noteworthy that thinning of the brain parietal cortex in the F 2 generation at post-natal day (PND) 11 was not associated with lesions or changes that were detectable by H&E histological examination.…”
Section: Discussionsupporting
confidence: 92%
“…Detailed reviews of animal evidence on the effects of developmental exposure to PBDEs on neurodevelopment are available [31,32,33]. In brief, Eriksson and colleagues conducted a series of experiments exposing neonatal mice to individual PBDEs (including BDE-47, BDE-99, BDE-153, BDE-183, BDE-203, BDE-206, and BDE-209) on either postnatal day 3, 10, or 19.…”
Section: Toxicologymentioning
confidence: 99%
“…Experiments performed in vivo have shown that the acute exposure of adult mice to TBBPA results in its selective accumulation in the striatum, which is accompanied by significant behavioral effects [24]. There are also indications that TBBPA may act as a developmental neurotoxin [20], although there has been a lack of consistency in studies describing the neurodevelopmental effects of TBBPA [38]. Studies performed in vitro using various cell cultures demonstrated the cytotoxicity of TBBPA and have identified several putative mechanisms, including disturbances in the intracellular signaling pathways, calcium imbalance, oxidative stress and excitotoxicity in neurons [5,22,25,27,28].…”
Section: Introductionmentioning
confidence: 98%